2020
DOI: 10.1111/jomf.12702
|View full text |Cite
|
Sign up to set email alerts
|

Divorce, Economic Resources, and Survival among Older Black and White Women

Abstract: This study identifies which midlife economic resources reduce the association between divorce and mortality risk among older Black and White women.Background: Despite evidence that divorce increases mortality risk due to economic losses, research has not established which among several common economic resources related to divorce are most important for older women's survival. There is also relatively little research on why marital inequalities in mortality are smaller among older Black women. Drawing from dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 64 publications
(109 reference statements)
0
4
0
Order By: Relevance
“…All models adjust for pandemic-related stressors (income loss, food insufficiency, delaying medical care due to the pandemic, and housing payment issues) and sociodemographic variables (gender, respondent’s age, race/ethnicity, educational attainment, household income, and whether any children under the age of 18 in the household). Previous studies have identified the importance of these pandemic-related stressors and these sociodemographic indicators in the association between relationship status and health ( Hearne 2021 ; Jace & Makridis 2021 ; Liu & Umberson 2008 ; Wolfe & Thomeer 2021 ). For income loss, respondents were asked, “Have you, or has anyone in your household, experienced a loss of employment income since March 13, 2020?” and “Do you expect that you or anyone in your household will experience a loss of employment income in the next 4 weeks because of the coronavirus pandemic?” If respondents responded yes to either question, they were coded as 1 for income loss, and if they responded no to both questions, 0.…”
Section: Methodsmentioning
confidence: 99%
“…All models adjust for pandemic-related stressors (income loss, food insufficiency, delaying medical care due to the pandemic, and housing payment issues) and sociodemographic variables (gender, respondent’s age, race/ethnicity, educational attainment, household income, and whether any children under the age of 18 in the household). Previous studies have identified the importance of these pandemic-related stressors and these sociodemographic indicators in the association between relationship status and health ( Hearne 2021 ; Jace & Makridis 2021 ; Liu & Umberson 2008 ; Wolfe & Thomeer 2021 ). For income loss, respondents were asked, “Have you, or has anyone in your household, experienced a loss of employment income since March 13, 2020?” and “Do you expect that you or anyone in your household will experience a loss of employment income in the next 4 weeks because of the coronavirus pandemic?” If respondents responded yes to either question, they were coded as 1 for income loss, and if they responded no to both questions, 0.…”
Section: Methodsmentioning
confidence: 99%
“…2 Finally, results from this study offer support to examining the distinct components of broad constructs such as wealth and debt. 2,16,23,35 Researchers often use overall indicators of wealth and debt when studying healthrelated disparities. 8 Using a single operationalization, for example, net worth, of wealth simplifies theoretical and statistical models but may conceal important relationships.…”
Section: Discussionmentioning
confidence: 99%
“…1,20,21 Although homeownership is the most common source of wealth, one's net worth can also drop owing to a loss in one's savings or in the value of other properties such as vehicles, real estate (beyond one's primary residence), and businesses or farms. Recent studies suggest that these components of net worth as well as large drops in their value can have independent associations with health and longevity, 16,22,23 but research has not considered whether this finding extends to obesity.…”
Section: Introductionmentioning
confidence: 99%
“…For many Black Americans, navigating the institutional and interactional racism of "white spaces" reduces the health advantages typically associated with higher education, occupational prestige, and wealth (Anderson 2022, Assari and Moghani Lankarani 2018, Phelan and Link 2015. This could also explain why previous research shows Black women's health is less closely tied to family processes (e.g., marriage, divorce, and childbearing) when compared to White women (Elwert and Christakis 2006, Roxburgh 2014, Wolfe and Thomeer 2021. That is, the economic gains White women tend to earn from marriage, or the educational losses associated with early motherhood, are less pronounced for Black women.…”
Section: Racism and Opportunity Constraintsmentioning
confidence: 99%